Incident-response monitoring technologies for aircraft-cabin air quality - Magoha, Paul W. (Kansas State University, 2012)
Poor air quality in commercial aircraft cabins can be caused by volatile organophosphorus (OP) compounds emitted from the jet engine bleed air system during smoke/fume incidents. Tri-cresyl phosphate (TCP), a common anti-wear additive in turbine engine oils, is an important component in today’s global aircraft operations. However, exposure to TCP increases risks of certain adverse health effects. This research analyzed used aircraft cabin air filters for jet engine oil contaminants and designed a jet engine bleed air simulator (BAS) to replicate smoke/fume incidents caused by pyrolysis of jet engine oil. Field emission scanning electron microscopy (FESEM) with X-ray energy dispersive spectroscopy (EDS) and neutron activation analysis (NAA) were used for elemental analysis of filters, and gas chromatography interfaced with mass spectrometry (GC/MS) was used to analyze used filters to determine TCP isomers. The filter analysis study involved 110 used and 74 incident filters. Clean air filter samples exposed to different bleed air conditions simulating cabin air contamination incidents were also analyzed by FESEM/EDS, NAA, and GC/MS. Experiments were conducted on a BAS at various bleed air conditions typical of an operating jet engine so that the effects of temperature and pressure variations on jet engine oil aerosol formation could be determined. The GC/MS analysis of both used and incident filters characterized tri-m-cresyl phosphate (TmCP) and tri-p-cresyl phosphate (TpCP) by a base peak of an m/z = 368, with corresponding retention times of 21.9 and 23.4 minutes. The hydrocarbons in jet oil were characterized in the filters by a base peak pattern of an m/z = 85, 113. Using retention times and hydrocarbon thermal conductivity peak (TCP) pattern obtained from jet engine oil standards, five out of 110 used filters tested had oil markers. Meanwhile 22 out of 74 incident filters tested positive for oil fingerprints. Probit analysis of jet engine oil aerosols obtained from BAS tests by optical particle counter (OPC) revealed lognormal distributions with the mean (range) of geometric mass mean diameter (GMMD) = 0.41 (0.39, 0.45) [mu]m and geometric standard deviation (GSD), [sigma][subscript]g = 1.92 (1.87, 1.98). FESEM/EDS and NAA techniques found a wide range of elements on filters, and further investigations of used filters are recommended using these techniques. The protocols for air and filter sampling and GC/MS analysis used in this study will increase the options available for detecting jet engine oil on cabin air filters. Such criteria could support policy development for compliance with cabin air quality standards during incidents.
Keywords: Smoke/fume incidents; Jet engine oils; Aircraft-cabin air quality; Tri-cresyl phosphate isomers; Aircraft-bleed air simulator; Aircraft-cabin air recirculation filters; Engineering (0537)